2016
DOI: 10.1021/acs.langmuir.5b04115
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–Solid Nanofriction and Interfacial Wetting

Abstract: Using atomic force microscopy, the nanofriction coefficient was measured systematically for a series of liquids on planar graphite, silica and mica surfaces. This allows us to explore the quantitative interplay between nanofriction at liquid-solid interfaces and interfacial wetting. A corresponding states theory analysis shows that the nanofriction coefficient, μ = dF(F)/dF(N), where FF is the friction force and FN is the normal force, is a function of three dimensionless parameters that reflect the intermolec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 53 publications
1
38
0
Order By: Relevance
“…Furthermore, unlike the slug-like velocity profiles in the graphene nanopore, the velocity profiles in quartz nanopore are parabolic, which are in agreement with the descriptions of the traditional Navier-Stokes equation [23,46]. Such different slip behavior of methane molecules on the quartz and graphene surface is interesting; the different liquid-solid interactions are generally regarded as the main reason, which is mainly dominated by the atom's parameters σ and ε [64,65] in Table 2 for the CH 4 molecules confined in various nanopores. In addition, the breakdown of gas molecules slippage on the quartz surface is especially owing to the inherent atomic roughness of the surface by Yu et al [43,66], especially, the potential energy roughness of the quartz surface is higher than that on graphene surface up to two magnitude of orders.…”
Section: Resultssupporting
confidence: 77%
“…Furthermore, unlike the slug-like velocity profiles in the graphene nanopore, the velocity profiles in quartz nanopore are parabolic, which are in agreement with the descriptions of the traditional Navier-Stokes equation [23,46]. Such different slip behavior of methane molecules on the quartz and graphene surface is interesting; the different liquid-solid interactions are generally regarded as the main reason, which is mainly dominated by the atom's parameters σ and ε [64,65] in Table 2 for the CH 4 molecules confined in various nanopores. In addition, the breakdown of gas molecules slippage on the quartz surface is especially owing to the inherent atomic roughness of the surface by Yu et al [43,66], especially, the potential energy roughness of the quartz surface is higher than that on graphene surface up to two magnitude of orders.…”
Section: Resultssupporting
confidence: 77%
“…Our experience has shown that surface wetting properties exhibit strong effects on the interfacial friction. [28] We thus examined the IL/oil wettability on Ti substrates, and observed no significant differences in contact angles (Table S1) of different IL/oil mixtures on Ti substrates, indicating the wetting behavior for different IL/oil This article is protected by copyright. All rights reserved.…”
Section: Resultsmentioning
confidence: 94%
“…Molecular simulation provides an attractive tool to elucidate such processes. [5][6][7][8][9][10][11] The results from molecular simulations of a given scenario are obtained by solving Newton's equation of motion and depend solely on the force field that describes the molecular interactions. If these interactions are reasonably described, the method has strong predictive capabilities.…”
Section: Introductionmentioning
confidence: 99%